Impact of time to radiation therapy in adjuvant settings in endometrial carcinoma: A multicentric retrospective study. (April 2020) - Neron, Mathias; Lambaudie, Eric; Thezenas, Simon; Leaha, Cristina; Kerr, Christine; Gonzague, Laurence; Provansal, Magali; Colombo, Pierre-Emmanuel; Fabbro, Michel
Highlights: Time to treatment (TTR) did not worse disease-free survival and overall survival. An impact of time to treatment on local recurrence rate could not be excluded. Robot-associated laparoscopy did not lengthen the treatment delay. Treatment delay seems highly dependent of health-care organization. Abstract: Objective: Time to adjuvant treatment could have an impact on cancer prognosis. It is possible that robotic surgery lengthens the healing time of vaginal cuff after minimally invasive hysterectomy. The objective of this study was to state the impact of time to RT (TTR) on prognosis in endometrial carcinoma (EC) patients and to assess variables associated with TTR. Study design: We conducted a multicentric retrospective study in two cancer centers. We included EC patients, between January 1996 and January 2016. We searched variables associated with TTR and impact of TTR on end-points: local recurrence-free survival, metastatic-free survival, event-free survival and overall survival. Results: 329 patients were included and 279 were analyzed for TTR impact. Robotic surgery was associated with shorter TTR (8 weeks, 8.9 w for laparotomy, 9.2 w for laparoscopy). Pelvic lymphadenectomy, para-aortic lymphadenectomy, discussion in multidisciplinary meeting and treatment center was independently associated with TTR. No impact of TTR was shown on metastatic-free survival, event-free survival and overall survival but there was a trend of a decreased local recurrence rate in case of prolonged TTR (HRcontinuous variable = 1.08; CI95 %: 0.97–1.2). Conclusion: Our study did not show any impact of treatment delay on survival end-points although prolonged TTR could moderate the benefit of radiotherapy on local control rate. Surgical route was not associated with TTR, particularly robot-associated laparoscopy did not lengthen treatment delay. TTR seems dependent of health-care organization and could represent a quality criterion of EC care for institutions.